LEGALITY EXTRAORDINARY GENERAL MEETING OF SHAREHOLDERS IMPLEMENTATION BY SHAREHOLDERS - Andhes Tan Satrisna (Indonesia Private Law Review, 2023)
The General Meeting of Shareholders (GMS) is the organ of the company that has the highest authority in the company, and all decisions relating to the company are stipulated through the GMS after certain conditions have been met as stipulated in the laws and regulations. The purpose of this research is to find out the implementation of the Extraordinary General Meeting of Shareholders (EGMS) and the legal consequences of the Implementation of the Extraordinary General Meeting of Shareholders organized by PT. KOLINGKAS in terms of Law Number 40 of 2007 concerning Limited Liability Companies. This study uses normative legal research methods and uses a qualitative approach. As well as using primary, secondary and tertiary sources of legal materials from books, journals, laws and regulations related to the holding of the Extraordinary General Meeting of Shareholders. The results of the study show that the legality of holding an EGMS by shareholders can be seen from the legal consequences of holding an Extraordinary General Meeting of Shareholders (EGMS) held by PT. KOLINGKAS, in holding the Extraordinary General Meeting of Shareholders, the Plaintiff as a Member of the Board of Directors was not given any defense by the Defendants, in this case PT. KLK and also the plan to dismiss the Plaintiff as Director were not notified in advance to the Plaintiff, the implementation was carried out unilaterally, or the directors did not know about it, so that the Plaintiff was dismissed by the EGMS as stated in Deed Number 06 concerning Minutes of the Extraordinary General Meeting of Shareholders of PT. KLK does not meet the requirements and procedures set out in UUPT and is an unlawful act, then it has violated laws and regulations or it is considered that the decision is legally flawed. So that for fraudulent acts committed by parties within the company, the party conducting the Extraordinary GMS activities can be held liable for civil liability for these actions.